Experiment and analysis of state preparation for atom interferometry - Zhang, Xu; Li, Qi-Xue; Zhang, Huan-Kai; Liu, Ji-Xun; Wang, Guo-Chao; Ma, Xiao-Xiao; Zhu, Ling-Xiao; Yan, Shu-Hua (Frontiers in Physics, 2024)
The state preparation is a crucial procedure in atom interferometry, however, there is a shortage of detailed experimental studies on determining the optimal method for achieving this. This paper investigates and compares two methods for state preparation: the combined use of microwave and Raman light (M-R), and the combined use of optical pumping, microwave and Raman light (O-M-W). The experimental results demonstrate that the M-R method improves the efficiency of Raman transitions for atom interference, which is helpful to enhance the contrast of the interference fringes. The O-M-R method increases the quantity of prepared atoms, thereby enhancing the signal-to-noise ratio of the detected signals. This work helps to provide a useful experimental basis and reference for researchers to design a suitable state preparation scheme.